Student Learning Motivation on Islamic Boarding School with Self Eficiacy As a Mediation Variabel - Komang Ade Komala Savitri; Satrio Wijoyo; Gilang Ramadhan; Hari Mulyadi (Didaktika: Jurnal Kependidikan, 2024)
The purpose of this research is to analyze student learning motivation on islamic boarding school with self efficiacy as a mediation variable in economic subjects. This type of research is quantitative research. This study uses the population of As-Syifa Boarding School Wanareja Integrated Islamic High School. The sample of this study was 270 students from class X, XI, XII. The data analysis technique used in this research is SEM-PLS which is processed with SmartPLS 3.0 software. The results of research conducted on economic subjects at As-Syifa Boarding School Wanareja Integrated Islamic High School are 1) Learning intention has a significant effect on self-efficiacy, 2) Learning intention has a significant effect on student learning motivation, 3) Parental support is influenced by self-efficiacy, 4) Parental support is influenced by student learning motivation, 5) Self eficiacy is influenced by student learning motivation, 6) Learning intention on student learning motivation is mediated in partial form by self-efficiacy, 7) Parental support on student learning motivation is mediated in partial form by self-efficiacy